Get in Touch With Dendritic Epithelial T Cells! - Thelen, Flavian; Witherden, Deborah A. (Frontiers in Immunology, 2020)
Innate and adaptive immune systems continuously interchange information and orchestrate their responses to protect the host. γδ T cells play crucial roles, as they incorporate both innate and adaptive immune characteristics. Dendritic epidermal T cells are specialized γδ T cells, which are uniquely positioned to rapidly respond to skin wounds and infections. Their elongated dendrite morphology allows them to be in continuous contact with multiple neighboring keratinocytes and Langerhans cells. Cellular interactions are fundamental to the formation, activation and maintenance of immune cell functions during steady state and pathology. Recent technological advances, especially in the field of cellular imaging, have contributed to the better characterization of complex cellular interactions in a spatiotemporally resolved manner. In this review, we will highlight the often-underappreciated function of DETC and other γδ T cells during steady state and an ongoing immune response. More specifically, we discuss how DETC-precursors are shaped in the fetal thymus during embryogenesis as well as how direct cell-cell interactions of DETC with neighboring cells in the epidermis shape skin homeostasis and effector functions. Furthermore, we will discuss seminal work and recent discoveries made in the γδ T cell field, which have highlighted the importance of γδ T cells in the skin, both in humans and mice.